Community-wide mask-wearing: a realistic approach amidst the second wave of Covid-19 in Pakistan - Rehan, Bahar; Farooqi, Maheera; Qureshi, Nazuk Eraj (Journal of the Pakistan Medical Association, 2021)
July - 2021